Catalytic degradation of phenols by recyclable CVD graphene films. Issue 13 (15th March 2018) - Yoo, Je Min; Park, Baekwon; Kim, Sang Jin; Choi, Yong Seok; Park, Sungmin; Jeong, Eun Hye; Lee, Hyukjin; Hong, Byung Hee
Abstract : This communication proposes the use of monolayer CVD graphene as a novel metal-free catalyst for degradation of phenols. Abstract : Ferrous ion-based catalysts have been widely employed to oxidatively destruct the major industrial pollutants such as phenolic compounds through advanced oxidation processes (AOPs). These agents, however, inevitably show several drawbacks including the need for pH adjustment and further purification steps to remove residual salts. Here we report the use of a chemical vapour deposition (CVD) graphene film as a novel metal-free catalyst for the AOP-based degradation of phenols in aqueous solution, which does not require additional steps for salt removal nor external energy to activate the process. We have also verified that the catalytic activity is strongly dependent on the surface area of the graphene film and the degradation efficiency can be markedly improved by exploiting an array of multiple graphene films. Finally, the recyclability of the graphene film has been validated by performing repetitive degradation tests to ensure its practical use.